Liver injury in children: signal analysis of suspected drugs based on the food and drug administration adverse event reporting system - Yan Liu; Hailong Li; Liang Huang; Chaomin Wan; Huiqing Wang; Xuefeng Jiao; Linan Zeng; Zhijun Jia; Guo Cheng; Lei Zhang; Wei Zhang; Lingli Zhang (BMC, 2023)
Abstract Background Evidence of drug-induced liver injury is abundant in adults but is lacking in children. Our aim was to identify suspected drug signals associated with pediatric liver injury. Methods Hepatic adverse events (HAEs) among children reported in the Food and Drug Administration Adverse Event Reporting System were analyzed. A descriptive analysis was performed to summarize pediatric HAEs, and a disproportionality analysis was conducted by evaluating reporting odds ratios (RORs) and proportional reporting ratios to detect suspected drugs. Results Here, 14,143 pediatric cases were reported, specifically 49.6% in males, 45.1% in females, and 5.2% unknown. Most patients (68.8%) were 6-18 years old. Hospitalization ranked first among definite outcomes (7,207 cases, 37.2%). In total, 264 disproportionate drug signals were identified. The top 10 drugs by the number of reports were paracetamol (1,365; ROR, 3.6; 95% confidence interval (CI), 3.4-3.8), methotrexate (878; ROR, 2.5; 95% CI, 2.3-2.7), vincristine (649; ROR, 3.0; 95% CI, 2.8-3.3), valproic acid (511; ROR, 3.2; 95% CI, 2.9-3.6), cyclophosphamide (490; ROR, 2.4; 95% CI, 2.2-2.6), tacrolimus (427; ROR, 2.4; 95% CI, 2.2-2.7), prednisone (416; ROR, 2.1; 95% CI, 1.9-2.3), prednisolone (401; ROR, 2.3; 95% CI, 2.1-2.5), etoposide (378; ROR, 2.3; 95% CI, 2.1-2.6), and cytarabine (344; ROR, 2.8; 95% CI, 2.5-3.2). After excluding validated hepatotoxic drugs, six were newly detected, specifically acetylcysteine, thiopental, temazepam, nefopam, primaquine, and pyrimethamine. Conclusions The hepatotoxic risk associated with 264 signals needs to be noted in practice. The causality of hepatotoxicity and mechanism among new signals should be verified with preclinical and clinical studies.